Sanitation and Hygiene Risk Factors Associated with Salmonella Contamination in Restaurant Foods in Makassar City: An Observational Cross-Sectional Study - Zaenab Zaenab; Sulasmi Sulasmi; Nurhaidah Nurhaidah (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Typhoid fever is an infectious disease that remains a public health concern in Indonesia, particularly in areas with inadequate sanitation. It is caused by Salmonella typhi, which is commonly transmitted through the consumption of contaminated food or water. Makassar City, as a major culinary hub, faces significant challenges in ensuring food safety across various restaurants. This study aims to analyze environmental exposure risks in restaurant food associated with typhoid fever incidence in Makassar City by identifying pathogenic microorganisms and assessing potential sources of contamination, including water quality, food material hygiene, environmental sanitation, and food handlers’ hygiene practices during food preparation and serving. This study employed an analytical observational design with a cross-sectional approach. A total of 60 restaurants were selected using purposive sampling based on location, type of business, and number of visitors. Data were analyzed using descriptive and inferential statistics (Chi-square test) to determine associations between risk factors and Salmonella sp. contamination in food. The findings revealed that environmental physical conditions (p = 0.002; OR = 6.25), food processing hygiene and sanitation (p = 0.009; OR = 4.67), food handlers’ personal hygiene (p = 0.042; OR = 3.60), and environmental contamination risk (p = 0.023; OR = 3.46) were significantly associated with Salmonella contamination. Restaurants that did not meet the required standards were more likely to have contaminated food compared to those that met the criteria. Meanwhile, risk control measures were not significantly associated with contamination (p = 0.405; OR = 1.55). In conclusion, strengthening hygiene and sanitation practices, implementing the Hazard Analysis and Critical Control Point (HACCP) system, and enhancing risk-based sanitation supervision by health authorities are essential to reduce typhoid transmission risks in restaurant settings.